Peru’s participation in the Security Council: Haiti, Democratic Republic of the Congo, and Timor-Leste - Morote Canales, Ricardo Estanislao (2021)
This article sets out Peru's contribution to the work of the Security Council during the 2006-2007 period. One of the main issues was the adjustment of the Security Council to a new post-Cold War agenda characterized by the emergence of intra-state conflicts in states displaced from progress with fragile institutions and, precarious development indicators that threatened international peace and security. Among the issues addressed by the Security Council, we will analyze the cases of Haiti, the Democratic Republic of the Congo, and Timor-Leste, in which Peru had more direct participation because it was a party to and led the "Group of Friends of Haiti" and the "Group of Friends of Timor-Leste" in 2006 and 2007 respectively. The Permanent Representatives of Peru to the United Nations served as Chairs of the Security Council Committee established under resolution 1533 (2004) concerning the Democratic Republic of the Congo in 2006 and 2007, respectively.